Northern perspectives on the Global South: principles of environmental education in Jonathan Foer - Alves Araújo, Gilberto (2026)
This article critically examines the environmental discourse advanced by Jonathan Safran Foer in We Are the Weather, drawing on critical ecopedagogy, decolonial thought, and climate justice frameworks. Through Critical Discourse Analysis, the study reveals how Foer’s narrative individualizes ecological responsibility and depoliticizes the climate crisis by promoting ethical consumption as the central solution. Although affective and ethical in tone, the discourse obscures structural causes such as colonialism, capitalism, and global inequalities, erasing insurgent knowledges from the Global South. The article argues that focusing on behavioral changes like vegetarianism perpetuates neoliberal and moralizing logics that hinder collective action and reinforce social disparities. It also explores how apocalyptic metaphors and the aesthetics of collapse act as rhetorical strategies that foster urgency while undermining political mobilization. In contrast, the study advocates for an insurgent ecopedagogy rooted in territorial struggles, Indigenous knowledge, and grassroots resistance as a viable alternative to consumer-centered pedagogy. The conclusion calls for systemic transformation integrating environmental and social justice, challenging neoliberal affective education through a politicized, collective, and hopeful praxis.